The brutal truth about Asian branding : and how to break the vicious cycle - Baladi, Joseph (Wiley, 2011)
"The world of Asian* brands is best characterized by complementary portions of confusion, delusion and outright ignorance by senior managers and brand owners. The net result is that the development of Asian brands has been arrested and significantly lags behind those in the West. Repeated surveys of Asians across the region confirm over and over again their overwhelming preference to drink Coke, wear Nike shoes and drive BMWs. Rare is the Apple zealot-like emotional relationship Asians will show for any Asian brand. Yet the region is awash with tens of thousands of new brands that emerge every other day reflecting an unstoppable energy and vitality that is fueling the increasingly universal belief that this century will belong to Asia (and China in particular). The continued absence of genuinely great Asian brands (as opposed to merely 'good' brands) will at best slow down that prospect, at worse throw a real spanner into the works. Sooner or later something needs to happen. And something will and in all likelihood it will be driven by individual visionary Asian business leaders. This book provides a clear and compelling blueprint that will deliver long-term sustainable competitive advantage to these exceptional leaders who will, in time, blaze a pioneering trail for others to follow ... (*Excluding Japanese brands)"--Publisher's site